Linking AKHLAK Culture to Engagement: The Mediating Role of Corporate Reputation - Sitanggang, Martua; Lubis, Rahmi; Turnip, Kaiman (Universitas Ahmad Dahlan, 2025)
This study investigates the mediating role of corporate reputation in the relationship between the AKHLAK work culture and work engagement among 270 employees at PT X in Medan. Utilizing a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS) analysis, the results indicate that: (1) the AKHLAK culture significantly enhances work engagement (β = 0.494, p < 0.05); (2) the AKHLAK culture positively influences corporate reputation (β = 0.640, p < 0.05); (3) corporate reputation has a significant positive effect on work engagement (β = 0.328, p < 0.05); and (4) corporate reputation partially mediates the relationship between AKHLAK culture and work engagement (β = 0.210, p < 0.05). Theoretically, this study contributes to the expansion of the Job Demands–Resources (JD-R) Model and Social Identity Theory by positioning corporate reputation as a novel mediating variable. Practically, the findings emphasize the strategic importance of integrating AKHLAK values with corporate reputation-building efforts to enhance employee engagement and organizational competitiveness. These insights offer actionable guidance for Indonesian state-owned enterprises (SOEs) aiming to align cultural initiatives with broader reputational goals, thereby strengthening both internal morale and external stakeholder perception. Keywords: work culture AKHLAK, corporate reputation, work engagement